Implementation of Enterprise Resource Planning (ERP) within Seven Clusters of the Warung Tegal "Bahari" Franchise Network in South Jakarta - Noviana Tursanurohmad; Burhan Bungin; Made Wilantara; Misnan (Commercium : Journal of Business and Management, 2026)
This study investigates how Enterprise Resource Planning (ERP) implementation reshapes organizational communication within the seven operational clusters of the Warung Tegal (Warteg) "Bahari" franchise in South Jakarta. While the network historically relied on informal coordination and manual bookkeeping, the introduction of ERP marks a strategic shift toward synchronized digital workflows. Using a qualitative descriptive design, data were gathered through in-depth interviews with 14 key informants, including franchisors, coordinators, and managers, alongside participant observations and document reviews. The findings reveal that ERP significantly enhances communication clarity and managerial transparency through real-time data flow and standardized reporting, effectively reducing the miscommunication common in manual systems. However, optimal implementation is hindered by critical barriers such as uneven digital literacy, limited training, and unstable internet connectivity. Furthermore, resistance to abandoning long-standing manual habits remains a challenge. The study concludes that while ERP provides a foundation for an accountable franchise model, its success depends on adaptive leadership and continuous digital capacity-building. These results offer practical insights for digital transformation in community-based culinary enterprises.